Developing Students Worksheets Using The Creative Thinking-Based Canva Application - Sugihandardji, Chumaedi; Binafsie, Latifah Ibda; Wardayani, Ari; Gunawan, Gunawan; Kusuma, Jaka Wijaya (International Journal of Multidisciplinary Research and Literature, 2025)
21st-century   education emphasises the importance of providing students opportunities to foster creative thinking, discover new solutions, and apply concepts to everyday life. One practical approach to encourage creative thinking during lessons is engaging materials or media, such as student worksheets (LKPD). This study aims to develop a mathematics teaching tool, specifically a student worksheet using the canva application based on creative thinking for eighth-grade statistics, which is both valid and practical. This research utilises a Research and Development (R&D) approach, employing the ADDIE model. The ADDIE development model includes five stages: analysis, design, development, implementation, and evaluation. Data analysis incorporates both qualitative and quantitative data. According to assessments from content and media experts, the developed LKPD was rated valid with an average score of 3.2. Student feedback surveys yielded a score of 3.25 (perfect), while teacher feedback surveys received a score of 3.47 (very good). Overall, the average score from student and teacher feedback was 3.36 (very good), indicating that the LKPD is practical for teaching. The developed student worksheet using the Canva application based on creative thinking for eighth-grade statistics is categorised as valid and practical for educational use.